(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This study aims to uncover the concealed personality folds within Balram’s character, highlighting the complex interplay of inferiority and superiority complexes, as framed by Alfred Adler’s theory. It examines how Balram’s relentless pursuit of superiority is influenced by his profound struggle with inferiority complex, shaping his character development. The research method employed in this study is qualitative by analyzing the character of Balram in the novel The White Tiger. The analysis technique used in this study comprises a content analysis of the novel The White Tiger. The study reveals that Balram’s character undergoes a significant transformation characterized by the development of a superiority complex. This transformation is rooted in his profound inferiority complex, which drives him to conceal and compensate for his perceived weaknesses. Exposure to Delhi’s high-end society exacerbates his inferiority complex, leading to low self-esteem and recurrent humiliation experiences. Finally, his relentless quest for dominance and revolutionary aspirations aligns with Adler’s concept of masculine protest. This study contributes to a deeper understanding of Balram’s character and the psychological complexities at play in his pursuit of superiority. It provides insights into the intricate layers of his personality, offering a nuanced analysis of how his inferiority complex shapes his behavior and motivations.